Current perspective on osteoarthritis: a narrative review - Pokhrel, Sony; Nepal, Ojashwi (Journal of Physiological Society of Nepal, 2021)
Introduction: Osteoarthritis is the most prevalent chronic inflammatory joint disease affecting mobility in humans. It is caused by inflammation, breakdown, and eventual loss of cartilage in the joints. It is one of the ten most disabling diseases in developed countries. In this review we aimed to appraise the current evidence for the short as well as long term prevention and available effective treatment approaches for osteoarthritis. The objective of this study is to discuss about the risk factors, clinical methods of treatment, prevention and recent development in pathophysiological understanding of osteoarthritis. Materials and methods: Full length published articles and journals were collected from different reliable sites, PubMed, Hinari and Medline. Among the accessed materials, 52 full length articles were selected excluding studies that only provided abstract as published papers. Results: The incidence and prevalence was high among the people who had suffered from joint injury or undergone joint surgery recently in their lives. The risk was also high in people with bone malalignment, altered shape of bone and muscle strength. High muscle/fat ratio showed a protective effect against KOA prevalence. The incidence also depends on age and sex, obesity, bone density and mass, diet and genetic factors. Conclusions: The risk is high among people with joint injury, old people, obese, people with poor diet, patients undergone joint surgery and in women after menopause. Definitive treatment for OA hasn’t been available yet but, there are ways for prevention and treatment of OA. Pharmacological treatment includes NSAIDs, non-pharmacological includes exercise, physical activity and diet whereas surgical method includes total joint replacement.